PERBAIKAN KADAR INSULIN TIKUS JANTAN GALUR WISTAR TERINDUKSI STREPTOZOTOCIN (STZ) AKIBAT PEMBERIAN EKSTRAK ETANOL BATANG BROTOWALI - Ashari, Ayu -; Nurinda, Eva; Fatmawati, Annisa (INPHARNMED Journal (Indonesian Pharmacy and Natural Medicine Journal), 2021)
Brotowali stems (Tinospora crispa L.) contain flavonoids which act as antioxidants and are expected to have the potential to reduce blood glucose levels and increase insulin levels in mice due to STZ induction. The purpose of this study was to determine the effect of brotowali stem ethanol extract (EEBB) on insulin levels in STZ-induced male Wistar rats. Measurement of mouse insulin levels using the mouse insulin ELISA kit method. The results showed that the ethanol extract of brotowali rods at a dose of 450 mg / kgBW rats were significantly different (<0.05) between the hyperglycemic control group and the EEBB treatment group showing an increase in the mean insulin levels of the rats after being given EEBB for 10 days. Brotowali stems can be used for the treatment of natural ingredients with flavonoid content.